2013
DOI: 10.2337/db12-0707
|View full text |Cite
|
Sign up to set email alerts
|

Early Metabolic Markers of the Development of Dysglycemia and Type 2 Diabetes and Their Physiological Significance

Abstract: Metabolomic screening of fasting plasma from nondiabetic subjects identified α-hydroxybutyrate (α-HB) and linoleoyl-glycerophosphocholine (L-GPC) as joint markers of insulin resistance (IR) and glucose intolerance. To test the predictivity of α-HB and L-GPC for incident dysglycemia, α-HB and L-GPC measurements were obtained in two observational cohorts, comprising 1,261 nondiabetic participants from the Relationship between Insulin Sensitivity and Cardiovascular Disease (RISC) study and 2,580 from the Botnia P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
292
4
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 328 publications
(337 citation statements)
references
References 42 publications
30
292
4
11
Order By: Relevance
“…However, this finding is in agreement with Bentley-Lewis et al (2015) who found that there are differences in metabolic levels, despite several similarities between T2DM and GDM [38]. Ferrannini et al (2012) observed that patients who developed T2DM later had increased BCAA levels, including those of leucine and valine, and of three major glucogenic amino acids (including arginine), whereas glycine was significantly decreased [44]. Scholtens et al (2014) found higher arginine levels in women with high fasting plasma glucose (FPG) (n = 67, 96.7 ± 20.6 µmol/l) than in women with low FPG (n = 49, 90.2 ± 15.7 µmol/l, p < 0.01).…”
Section: Resultssupporting
confidence: 86%
“…However, this finding is in agreement with Bentley-Lewis et al (2015) who found that there are differences in metabolic levels, despite several similarities between T2DM and GDM [38]. Ferrannini et al (2012) observed that patients who developed T2DM later had increased BCAA levels, including those of leucine and valine, and of three major glucogenic amino acids (including arginine), whereas glycine was significantly decreased [44]. Scholtens et al (2014) found higher arginine levels in women with high fasting plasma glucose (FPG) (n = 67, 96.7 ± 20.6 µmol/l) than in women with low FPG (n = 49, 90.2 ± 15.7 µmol/l, p < 0.01).…”
Section: Resultssupporting
confidence: 86%
“…In addition, various lipid species and lipid fractions [85,[87][88][89][90], as well as other small metabolites [87,89,91], showed significant associations with the risk of type 2 diabetes or incident impaired glucose metabolism after adjustment for multiple confounders. Some of the aforementioned studies compared the accuracy of prediction models without and with metabolites (Table 2) and found fairly modest improvements in AROCs for models that included metabolomics in addition to established risk factors for type 2 diabetes [84,88,89,91].…”
Section: Lipids and Small Metabolitesmentioning
confidence: 96%
“…Very recently, data on lipids and small metabolites have become available from prospective studies, and these are summarised in Table 2 [84][85][86][87][88][89][90][91]. These studies showed that elevated levels of branched-chain and aromatic amino acids and lower levels of glycine are associated with incident type 2 diabetes or deteriorating glucose homeostasis [84,[86][87][88][89][90].…”
Section: Lipids and Small Metabolitesmentioning
confidence: 99%
“…43 In the Botnia study, α-HB was found to be a positive predictor and L-GPC a negative predictor of progression to T2DM. 45 …”
Section: Metabolite Biomarkers Of Insulin Resistancementioning
confidence: 99%